The Effectiveness of Variations in Contact Time and Density of Water Hyacinth Plants in Reducing COD Level in Tofu Industrial Wastewater - Wahyu Rizki Nur Cahyani; Tri Joko; Nikie Astorina Yunita Dewanti (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Tofu industry X is one of 24 tofu industries in Bandungan, producing wastewater with a high organic matter content of 600 liters per day. The industry does not have a waste treatment plant and is directly discharged into water bodies, leading to environmental pollution. The phytoremediation method uses water hyacinth plants to be inexpensive and efficient. This study aims to see the effectiveness of water hyacinth plants in reducing COD levels in tofu wastewater. The method used quasi-experimental with a pretest-posttest control group design. The independent variables were contact time (2 and 4 days) and water hyacinth plant density (2 individuals/m2, 4 individuals/m2, and 6 individuals/m2), for the dependent variable was a decrease in COD levels tofu wastewater. 39 samples were tested and analyzed by the Kruskal Wallis test. The results showed the effectiveness of reducing COD levels by 78.68% (2 days) and 80.15% (4 days) for a density of 2 individuals/m2, 80.56% (2 days) and 86.58% (4 days) for density of 4 individuals/m2, and 83.79% (2 days) and 87.33% (4 days) for a density of 6 individuals/m2. It can be concluded that water hyacinth plants efficiently reduce COD of tofu wastewater but have not been effective in reducing COD to quality standards. There is a significant difference in reducing the COD levels of tofu wastewater using the treatment methods.